Economic impacts and determinants of foreign direct investment in Malaysia - Sabariah Nordin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The flows of world foreign direct investment (FDI) have been increasing; however, there has been a shift in the inflows of FDI from developed to developing countries. The shift raises questions on the factors that have attracted the inflows of FDI despite the benefits believed to be brought by FDI on the host economy. Thus, the objectives of this study are to examine determinants of inward flows of FDI, determine the impact of FDI on economic growth and examine the impact of FDI on employment, particularly in Malaysia. In examining the determinants of FDI, this study employed the bounds test (ARDL) approach for the study period between 1970 to 2009. Results indicate the existence of co-integration relationships among underlying variables. Trade openness and exchange rates are found to be the most robust and consistent variables in the short run and long run. Trade openness is found to be positive and significant, while exchange rates are found to be negative and significant in influencing the inward flows of FDI. In determining the impact of FDI on economic growth, this study utilized the Johansen-Juselius VECM approach for the period between 1970 to 2012. Based on the model which comprised of real GDP, FDI, trade openness and government development expenditure, this study proves the existence of a long run relationship among the variables with FDI and trade openness exert a positive and significant influence on the Malaysian economic growth. Finally, in examining the impact of FDI on the Malaysian employment condition, this study applied a panel data analysis of pooled, random and fixed effects models. The underlying variables are employment, FDI, real wages and gross output of five different sub-sectors for the period between 2000 to 2010. Results of robust fixed effects indicate that only the gross output is positive and significant in influencing employment.